Primula mianyangensis (Primulaceae), a new species from Sichuan, China - Wu, Xing; Xu, Yuan; Hu, Chi-Ming; Hao, Gang (Phytotaxa, 2013)
A new species assigned to Primula section Aleuritia Duby is described and illustrated under the name P. mianyangensis G.Hao & C.M.Hu. The new species resembles P. socialis Chen & C.M.Hu in lacking a scape and having farinose leaves, but differs by its much taller stature, long-petioled leaves and larger flowers.